The Missing Solar Cycle Response of the Polar Summer Mesosphere. Issue 16 (26th August 2019) - Hervig, Mark E.; Siskind, David E.; Bailey, Scott M.; Merkel, Aimee W.; DeLand, Matthew T.; Russell, James M.
Abstract: The response of the polar mesosphere to the 11‐year solar cycle is investigated using satellite observations from 1979 to 2018. Solar maximum is expected to cause higher temperatures and lower water vapor in the upper mesosphere, thus reducing the amount of ice in polar mesospheric clouds (PMCs). While PMCs showed a clear anticorrelation with the solar cycle before roughly 2002, this response is absent during recent years. PMCs are controlled by temperature and water vapor, which were examined using mesospheric observations during 1992–2018. The main cause of the diminished solar cycle in PMCs near 68°S and 68°N appears to be a dramatic suppression of the solar cycle response of water vapor. The solar cycle response of temperature also decreases after 2002, but calculations show that the decreased H2 O response had more than 3 times the impact on PMCs than the reduction in temperature response. Key Points: The response of PMCs to the 11‐year solar cycle was strong before ~2002 but is absent after The change in PMCs is mostly due to a suppression of the solar cycle response of water vapor The solar cycle in temperature is reduced after ~2002 but has a secondary effect on PMCs